Clinical features of pulmonary infarction in older patients with pulmonary embolism: a retrospective comparative study - Xing, Zhen-Chuan; Yuan, Yuan; Zhang, Hong-Xia; Wang, Jin-Xiang; Zhang, Shuai (Frontiers in Medicine, 2025)
ObjectiveTo analyze the clinical characteristics of pulmonary infarction in older patients with pulmonary embolism.MethodsWe conducted a single-center retrospective study of 71 patients with pulmonary infarction (PI) secondary to pulmonary embolism (PE) confirmed by CTPA between January 2016 and December 2021. Participants were stratified into older (≥65 years) and non-older (<65 years) groups. We compared baseline characteristics, laboratory/imaging findings, Wells scores, PE severity, diagnosis and treatment using chi-square and Mann-Whitney U tests.ResultsPI occurred in 17.1% (71/414) of PE cases, comprising 36 older patients and 35 non-older patients. Significant differences were observed in pleuritic chest pain, hemoptysis, cardiovascular disease, cerebrovascular disease, pulmonary hypertension, and ECG changes between the two groups (P < 0.05). PI occurred predominantly in the right lung and in lower lobes. No significant differences were observed in infarction location, number, or imaging signs between groups. The comparison of PE risk factors and Wells scores showed no significant differences. The older group showed a higher proportion of intermediate-high risk and a lower proportion of low-risk in PE severity classification (P < 0.05). During the medical consultation process, older exhibited higher non-emergency/respiratory first-visit rates than younger (P < 0.05). Similarly high rates of antibiotic therapy were observed in both groups (P > 0.05).ConclusionOlder PI patients have less typical chest pain, hemoptysis or ECG changes, a high proportion of comorbid cardiovascular/cerebrovascular diseases, and a higher rate of mismatch in the first visiting department. Clinicians should recognize the atypical presentations of PI in older patients and pay increased attention to this population.